2014
DOI: 10.1093/ajh/hpu033
|View full text |Cite
|
Sign up to set email alerts
|

Placental Expression of proBNP/NT-proBNP and Plasma Levels of NT-proBNP in Early- and Late-Onset Preeclampsia

Abstract: The results indicate possible placental production and release of proBNP/NT-proBNP into the maternal circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…Alternatively, increased cardiac load and elevated serum levels of NT-proBNP/BNP may be two independent components of a relatively heterogeneous preeclampsia syndrome. Moreover, it should be remembered that a fraction of circulating NT-proBNP/BNP is released from the placenta [ 23 ].Our findings are consistent with the results of previous studies in which patients with PE and GH presented with significantly higher serum levels of NT-proBNP than women with uncomplicated pregnancies. Furthermore, we showed that elevated serum level of NT-proBNP is a significant indicatorof PE and GH.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, increased cardiac load and elevated serum levels of NT-proBNP/BNP may be two independent components of a relatively heterogeneous preeclampsia syndrome. Moreover, it should be remembered that a fraction of circulating NT-proBNP/BNP is released from the placenta [ 23 ].Our findings are consistent with the results of previous studies in which patients with PE and GH presented with significantly higher serum levels of NT-proBNP than women with uncomplicated pregnancies. Furthermore, we showed that elevated serum level of NT-proBNP is a significant indicatorof PE and GH.…”
Section: Discussionmentioning
confidence: 99%
“…So far, NT-proBNP, an unspecific marker for pregnancy complications such as preeclampsia as well as for heart failure and other diseases, is markedly elevated in most PPCM patients with little overlap to healthy peripartum women ( Table 1 ). 23 , 39 , 40 MiR-146a is specifically increased in the serum of PPCM patients compared with healthy postpartum women and patients with DCM ( Table 1 ). 23 , 38 sFlt1, a biomarker for preeclampsia that is supposed to clear rapidly after delivery, is significantly increased in PPCM patients as are asymmetric dimethyl arginine and Cathepsin D activity ( Table 1 ).…”
Section: Biomarkers For Diagnosis and Risk Stratification Of Peripartmentioning
confidence: 99%
“…Three studies reporting on NTproBNP described elevated levels in pre-eclampsia vs. controls with P = 0.0103 ( Figure 6), [85][86][87] with insufficient studies for meta-analyses.…”
Section: Insulin Plasma Glucose and Fatty Acid-binding Proteinmentioning
confidence: 99%